FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI STRATEGI YANG EFEKTIF DALAM INDUSTRI BANK SYARIAH - Marlizar Marlizar (Universitas Muhammadiyah Aceh, 2018)
This paper aims to review some researches on the factors affecting effective strategy implementation in Islamic banks industry. The expected of this review is to provide benefits for related researches in the future. This study uses some empirical studies and review papers related to the factors affecting effective strategy implementation in Islamic banks industry. The analysis allows to identify interesting points for future research on the topic of the factors affecting effective strategy implementation in Islamic banks industry. This paper provides a better understanding on how to measure the factors affecting effective strategy implementation in Islamic banks industry in enhancing their performance. This paper only reviewed concerned articles from ScienceDirect and Emerald Insight. The results of the review showed that the limited studies about the factors affecting effective strategy implementation in Islamic banks industry. Result of this study is believed to give worth understanding about actual situation in this field of research. It proposed some notions that will stimulate more intensive researches in this field in the future.Keywords: Â Strategy implementation factors, strategy execution, performance and Islamic Bank Industry